To solve the system of equations by elimination, we'll add the two equations together to eliminate the variable "y":
(3x + 4y) + (2x - 4y) = 31 + (-6)
Combining like terms:
5x = 25
Divide both sides by 5 to solve for x:
x = 5
Now substitute the value of x back into either of the original equations, let's use the first equation:
3(5) + 4y = 31
15 + 4y = 31
Subtract 15 from both sides:
4y = 16
Divide both sides by 4 to solve for y:
y = 4
So the solution to the system of equations is (x, y) = (5, 4).
Therefore, the correct response is:
(5, 4)
Solve the system of equations by elimination.%0D%0A%0D%0A3x + 4y = 31%0D%0A2x – 4y = –6%0D%0A(1 point)%0D%0AResponses%0D%0A%0D%0A(4, 5)%0D%0A(4, 5)%0D%0A%0D%0A(5, 4)%0D%0A(5, 4)%0D%0A%0D%0A(–5, 12.5)%0D%0A(–5, 12.5)%0D%0A%0D%0A(5, –4)
1 answer